Beef Carcass Contamination by Shiga Toxin-Producing Escherichia coli Strains in an Abattoir in Brazil: Characterization and Resistance to Antimicrobial Drugs - Rigobelo, Everlon Cid [UNESP]; Santo, Edilene [UNESP]; Marin, Jose Moacir (Mary Ann Liebert, Inc., 2008)
A survey was performed to estimate the frequency of Escherichia coli and Shiga toxin-producing E. coli (STEC) in carcasses obtained from an abattoir in Brazil between February 2006 and June 2007. A total of 216 beef carcasses were sampled at three stages of the slaughter process-preevisceration, postevisceration, and postprocessing-during the rain and dry seasons, respectively. of the carcasses sampled, 58%, were preevisceration E. coli positive, 38% were postevisceration positive, and 32% postprocessing positive. At the postprocessing stage, the isolation of E. coli was twice as high in the rain season. E. coli was isolated from 85 carcasses of which only 3 (1.4%) were positive for stx-encoding genes. No E. coli O157 serogroup isolates were detected. No antimicrobial resistance was found in nine of the isolates (10% of the total). The most frequent resistances were seen against cephalothin (78%), streptomycin (38%), nalidixic acid (36%), and tetracycline (30%). Multidrug resistance (MDR) to three or more antimicrobial agents was determined in 28 (33%) E. coli isolates. The presence of STEC and MDR strains among the isolates in the beef carcasses emphasizes the importance of proper handling to prevent carcass contamination.